PENERAPAN KEBIJAKAN E-GOVERNMENT (UKG ONLINE) TERHADAP KINERJA GURU SMP - Nurmalita Dwiyanti; Abdullah Abdullah (Faculty of Economic and Business, University of Pasundan, 2019)
E-government in Indonesia is not currently running well, the ranking of Indonesia in EGDI was a decline in 2016 to number 116. One of e-government implementation in education is online teacher competency examination. This research aims to find out the implementation of e-government policy through online teacher competency examination, result of online teacher competency examination, teachers’ performance in Junior High School, and finds out its relationship. The research was conducted using UTAUT model. Data were collected from online teacher competency examination’s results, and teacher performance assessment. The sample is determined by technique of convenience sampling, counted 77 respondents. The results show that the implementation of e-government through online teacher competency examination is good. Online teacher competency examination’s results showed that the average teacher is still in coaching category. The teachers’ performance is good. However, there’s no relationship between the implementation of e-government and online teacher competency examination on teachers’ performances simultaneously or partially.